PERAYAAN MAULID DICIKOANG:SELAYANG PANDANG TAREKAT DI MAKASSAR - Supratman, Supratman; masdiana, masdiana (JURNAL ILMU BUDAYA, 2014)
Sayyid Jalaluddin al-Aidid was the 27th generation descendant of the Prophet, from Iraq, whom'Sayyid Community' attributed to him in Cikoang. The teachings of Sayyid Jalaluddin Al-Aidid are a heavily mystical dimension that is "Baharul Nur" (Ocean of Divine Light). Bahar ul Nur(Sea of Light Divine) is just a different name of Nur Muhammad.Cikoang community is part of the Shiite theosophy, but jurisprudence (Fiqh) adheres to SunniShafi'i. Cikoang community, according to the teachings of Sayyid Jalaluddin, argued that a trueMuslim has the main and first task was to honor the prophet's birthday celebrated in the mostluxurious. All other religious obligations (including the five daily prayers) they called secondaryof the prophet birthday. Celebrating a birthday for the Cikoang citizens is equivalent withpilgrimage.Traditionally, religious education in Cikoang has four degrees are: Angngaji is to teach writingand reading of the Koran; Assarapa is to study and understand Arabic grammar; Assarea is tolearn about Islamic law (Sharia) in Arabic and Makassar, and Attareka is finaly learning aboutgnosis (ma'rifat) and spiritual truth.Keywords: Sayyid Jalaluddin Al-Aidid, Shiite, Cikoang, Anggaji, Assarapa, Assarea, Attareka,Baharul Nur, Nur Muhammad.